Quantitative evaluation of the decarburization and microstructure evolution of WC–Co during plasma spraying - Zhan, Qing. (2013)
The major hurdle that limits extensive application of thermal sprayed WC–Co coatings is the undesirable phase changes from WC to W2C or even W due to loss of carbon. This study investigated quantitatively the decarburization of WC in both in-flight and coating formation stages during atmospheric plasma spraying. The microstructure evolution of WC particles accompanying the decarburization was also investigated. Results showed that decomposition and oxidation of WC to W2C predominantly occurred in the in-flight stage (75.82%), while remnant 24.18% occurred during the coating formation stage. Further carbon loss during the coating formation stage of WC–Co droplets is dependent significantly on the temperature of the substrate/pre-coating. Most of the irregular WC particles turned into rounded morphology with a significant decrease in size. W2C precipitated from the liquid matrix showed either columnar growth or epitaxial growth on WC substrate.